Cultural adaptation of the Italian version of the Patient-Reported Outcomes Common Terminology Criteria for Adverse Event (PRO-CTCAE®). Issue 3 (June 2023) - Caminiti, Caterina; Bryce, Jane; Riva, Silvia; Ng, Diane; Diodati, Francesca; Iezzi, Elisa; Sparavigna, Lucia; Novello, Silvia; Porta, Camillo; Del Mastro, Lucia; Procopio, Giuseppe; Cinieri, Saverio; et al.
Introduction: US National Cancer Institute's (NCI) Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE ® ) is a library of 78 symptom terms and 124 items enabling patient reporting of symptomatic adverse events in cancer trials. This multicenter study used mixed methods to develop an Italian language version of this widely accepted measure, and describe the content validity and reliability in a diverse sample of Italian-speaking patients. Methods: All PRO-CTCAE items were translated in accordance with international guidelines. Subsequently, the content validity of the PRO-CTCAE-Italian was explored and iteratively refined through cognitive debriefing interviews. Participants (n=96; 52% male; median age 64 years; 26% older adults; 18% lower educational attainment) completed a PRO-CTCAE survey and participated in a semi-structured interview to determine if the translation captured the concepts of the original English language PRO-CTCAE, and to evaluate comprehension, clarity and ease of judgement. Test-retest reliability of the finalized measure was explored in a second sample (n=135). Results: Four rounds of cognitive debriefing interviews were conducted. The majority of PRO-CTCAE symptom terms, attributes and associated response choices were well-understood, and respondents found the items easy to judge. To improve comprehension and clarity, the symptom terms for nausea and pain were rephrased and retested in subsequent interview rounds. Test-retest reliability was excellent for 41/49 items (84%); the median intraclass correlation coefficient was 0.83 (range 0.64-0.94). Discussion: Results support the semantic, conceptual and pragmatic equivalence of PRO-CTCAE-Italian to the original English version, and provide preliminary descriptive evidence of content validity and reliability.